2021
DOI: 10.1146/annurev-psych-010419-050815
|View full text |Cite
|
Sign up to set email alerts
|

Memory and Sleep: How Sleep Cognition Can Change the Waking Mind for the Better

Abstract: The memories that we retain can serve many functions. They guide our future actions, form a scaffold for constructing the self, and continue to shape both the self and the way we perceive the world. Although most memories we acquire each day are forgotten, those integrated within the structure of multiple prior memories tend to endure. A rapidly growing body of research is steadily elucidating how the consolidation of memories depends on their reactivation during sleep. Processing memories during sleep not onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(77 citation statements)
references
References 165 publications
2
75
0
Order By: Relevance
“…As with pre-stimulus effects, investigators have also reported post-encoding or post-learning reactivation effects in the hippocampus and other structures, either during sleep or rest, that predict subsequent memory in rodents (Silva et al, 2009;Sutherland & McNaughton, 2000;Wilson & McNaughton, 1994) and humans (de Voogd et al, 2016;Dudai et al, 2015;Gruber et al, 2016;Hermans et al, 2017;Paller et al, 2021;Staresina et al, 2013;Tambini & Davachi, 2019). It is noteworthy that not only changes in HPC activity alone, but also in its functional connectivity with other structures, correlated with subsequent memory, suggesting that they reflect early memory consolidation processes.…”
Section: Mpfc and Hippocampus In Formation Of Episodic Memories: Pre-stimulus And Postencoding Effects On Consolidationmentioning
confidence: 99%
“…As with pre-stimulus effects, investigators have also reported post-encoding or post-learning reactivation effects in the hippocampus and other structures, either during sleep or rest, that predict subsequent memory in rodents (Silva et al, 2009;Sutherland & McNaughton, 2000;Wilson & McNaughton, 1994) and humans (de Voogd et al, 2016;Dudai et al, 2015;Gruber et al, 2016;Hermans et al, 2017;Paller et al, 2021;Staresina et al, 2013;Tambini & Davachi, 2019). It is noteworthy that not only changes in HPC activity alone, but also in its functional connectivity with other structures, correlated with subsequent memory, suggesting that they reflect early memory consolidation processes.…”
Section: Mpfc and Hippocampus In Formation Of Episodic Memories: Pre-stimulus And Postencoding Effects On Consolidationmentioning
confidence: 99%
“…How do we strengthen memories while we sleep? The prime vehicle of systems consolidation is thought to be the reactivation of information encoded during prior wakefulness 1 4 . Through reactivation, memory representations are relayed between the hippocampus and neocortical long-term stores, transforming initially labile representations into long-lasting memories during sleep 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%
“…48 In addition, novel approaches to promote health and well-being could be explored. 49 Neural decoding methods 2-5 could also be applied in various creative ways. Based on the current results, we suggest that future studies might consider shorter intervals for sleep staging (to avoid cases where part of an interval is REM with two-way communication, followed by an awakening, requiring the entire interval be designated as wake, as occurred sometimes in our studies).…”
Section: Open Accessmentioning
confidence: 99%